Biopolymer Systems in Soft Tissue Engineering: Cell Compatibility and Effect Studies including Material, Catalyst, and Surface Properties - Hege, Cordula S.; Siegel-Axel, Dorothea; Kohler, Konrad; Delorme, Nicolas; Le Houérou, Vincent; Schiller, Stefan M.; Dolderer, Jürgen H. (ACS Applied Polymer Materials, 2020)
Cell compatibility of biomaterials is one of the most important issues in tissue engineering. It is affected by the catalyst, the chemical composition, and the surface topography of the material. Our aim was to study the influence of these factors for three standard FDA-Approved biopolymers on the proliferation of preadipocytes. The analyzed materials were polyesters, which were synthesized by ring-opening polymerization. Tin(II) octanoate is the standard catalysts for the ring-opening polymerization; however, it is considered to be cytotoxic. Therefore, we compare its compatibility with iron catalysts. Our study suggests that neither polymers nor catalysts or mechanical properties have a significant impact on cell compatibility in short-Term 2D cell cultures in vitro. In contrast, nanoroughness can influence how cells attach and spread in a material, showing an influence on preadipocyte proliferation. Higher nanoroughness leads to higher cell compatibility, which becomes more pronounced with time.
CRIS-Team Scopus Importer:2024-12-11
Keywords: biocompatibility; biomaterial; biomedicine; biopolymer; polyesters; surfaces; tissue engineering